Guitar improvisation: the concept of improvisation (au privave by Charlie Parker) / Syed Aizuddin Asraf Syed A. Rahman - Syed A. Rahman, Syed Aizuddin Asraf (2013)
The purpose of this study is to investigate the concept of improvisation among modern guitar music students. The study was involved 5 degree guitarist students in Music in Performance UiTM Shah Alam.. This research used a qualitative approach, where it discusses the improvisation method being used by the student. The methodology being for this study involved 13 questions that specifically focused on the improvisation technique. The findings from this research was analyzed and all of the respondent's answers to the questionnaire and interview were compared to see the differences and similarities.